SOCIOCULTURAL DYNAMICS IN THE CONTEXT OF GLOBALIZATION - Абисова, М. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article focuses on the basic characteristics of the transformational impact caused by globalization on social institutions, man and culture.